Dynamics of Supply Chain in Retail Sector - Garg, Sachin (2007)
Supply chain management is becoming very essential for any company for its growth and success. In today's dynamic world, rapidly changing technologies have significant effects on virtually all areas of business, which are expressed in terms of opportunity and threats, including supply chain of goods and services in the marketing channels. These new changing technologies provide opportunity to firms. The company needs to function under an efficient supply chain system where the customers can get maximum satisfaction. A proficient supply chain should concern suppliers, retailers and distributors getting appropriate profits with final consumer getting the value for their money spent and importantly product satisfaction.